PEMERTAHANAN BAHASA BALI DALAM RANAH KELUARGA DAN RANAH AGAMA DI DESA SEDAHAN JAYA - Putri, Rani Annisa; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
This study was conducted in three generations of adult, old and young generation. Problems discussed in this study, namely. (2) How is the mastery of Balinese language in terms of the four aspects of language skills in Sedahan Jaya Sukadana Village, Kayong Utara District, (3) What is the language of Balinese people in the village of Sedahan Jaya Sukadana, supporting factors and drawing of Balinese language defense of Balinese Sedahan Jaya Sukadana community of Kayong Utara Regency. The method used in this study is a mix method or two methods used in one study. The method is a qualitative and quantitative method. In addition, other methods used are methods of observation and interview. The data in this study are questionnaires and interviews that have involved adult, elderly and younger generations. Data collection techniques used in this study is a recording technique and recording techniques and simple calculations using SPSS version 20 applications. Based on the data analysis Balinese language defense in the realm of family and religion in Sedahan Jaya Village can be concluded that although the people of Bali use a second language but they still maintain their traditional language or mother tongue.Â Keywords: Language defense, Balinese language, sociolinguisticsÂ